Quasi-convexity and Hermite-Hadamard type inequalities - Alawiah Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this paper, some inequalities connected with the left and right hand side of Hermite- Hadamard type inequalities are established for functions whose the first and second derivatives absolute values are quasi-convex.